Unity in Christ: bishops, synodality, and communion - Fisher, Anthony (Catholic University of America Press, 2023)
Intro -- Contents -- Abbreviations -- Foreword by Cardinal Mario Grech -- Acknowledgments -- Introduction -- Part I: Sources -- 1. Fraternity and Communio among the Apostles -- 2. Episcopal Fraternity and Communio in the Tradition -- 3. Vatican II on Collegiality and Pope Francis on Synodality -- Part II: Living Episcopal Unity -- 4. Episcopal Spirituality -- 5. Episcopal Friendship -- 6. Episcopal Preaching -- Concluding Reflections -- Bibliography -- Notes -- Index.